Worse survival of hepatocellular cancer patients with membranous insulin receptor overexpression - Steffen Markus Heckl; Carolin Schneider; Lukas Kercher; Hans-Michael Behrens; Jan-Paul Gundlach; Alexander Bernsmeier; Stephan Schmidt; Sandra Krüger; Felix Braun; Rainer Günther; Thomas Becker; Stefan Schreiber; et al. (Scientific Reports)
Abstract Hepatocellular cancer (HCC) therapy is in need for an ideal companion diagnostic. Preclinical experimental studies have identified the insulin receptor (IR) and its synergistic counterpart, the IGF1 receptor (IGF1R), as relevant in HCC development, and the ligands IGF1 and IGF2 have been found to be elevated in HCC. This study aimed to bridge the gap to the clinical setting and explore whether the IR or the IGF1R would be of prognostic significance and would be associated with clinicopathologic parameters in HCC patients. In our retrospective cohort study located at the University Hospital Schleswig-Holstein, Campus Kiel, Germany, HCC samples of 139 patients were examined for IR and IGF1R expression by immunohistochemistry. A HistoScore was correlated with clinicopathological characteristics and survival. IR overexpression was frequently observed and was associated with clinicopathological parameters and survival. Membranous IR expression was associated with worse tumor specific survival (p = 0.043). Intriguingly, membranous IR expression was associated with worse tumor specific survival (p = 0.017) in the subgroup of patients undergoing sorafenib therapy. IGF1R expression was not associated with survival. In conclusion, our results suggest that membranous IR expression plays a role in HCC prognosis and treatment resistance, inspiring future validation as a potential companion diagnostic in HCC.